Original paperMetabolic syndrome in psoriasis - Szponar-Bojda, Anna; Krasowska, Dorota; Pietrzak, Aldona; Chodorowska, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Recent years’ studies have revealed a link between the metabolic syndrome and psoriasis. The common elements of pathogenesis of both diseases, primarily associated with severe inflammation, may be responsible for an increased incidence of metabolic syndrome components in psoriasis patients. Aim: To evaluate the prevalence of selected risk factors for the metabolic syndrome in patients with psoriasis and possible involvement of these factors in the severity of psoriasis. Material and methods : The study included 117 adult psoriatic patients compared with a control group. The severity of psoriasis was evaluated using the PASI and mNAPSI score. Basic laboratory tests were performed. The body mass index (BMI), De Ritis ratio and blood pressure were determined for each patient. Results : In the psoriasis group, excess body weight and abnormal values of BMI were significantly more frequent. Body mass index and body weight were significantly higher in patients with the calculated De Ritis ratio than in other subjects. The levels of erythrocyte sedimentation rate and C-reactive protein were significantly higher in the psoriasis group and positively correlated with BMI. Compared with controls, patients with psoriasis had significantly higher values of systolic and diastolic blood pressure, with no correlation with the severity of psoriasis evaluated using the PASI and mNAPSI score. Conclusions : The results obtained in our study indicate that psoriatic patients appear to be at a higher risk of the metabolic disorders such as hypertension, obesity, liver dysfunction, increased inflammatory parameters than healthy subjects, irrespective of the full manifestation of the metabolic syndrome. We suggest that patients with psoriasis should be routinely screened for the presence of the above-mentioned disorders.